2015
DOI: 10.1186/s40064-015-0966-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of glutathione S-transferase (GSTM1 and GSTT1) genes with chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML), as most of cancers results from a complex interaction between genetic or non genetic factors. Exposures to xenobiotics endogenous or exogenous associated with a reduced individual ability in detoxifying activity, constitutes a risk of developing cancer. It is known that polymorphism of glutathione S-transferases (GSTs) genes affects the detoxification of xenobiotics. Thus, we conducted a case-control study in which 92 patients (Mean age ± SD, 40.62 ± 12.7 years) with CML and 93 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
2
17
1
2
Order By: Relevance
“…The above findings were in agreement with a recent study conducted in Sudan (Muddathir et al, 2019). Many studies have focused on the relationship between GSTT1 polymorphism and the risk of CML in diverse ethnic groups (Bajpai et al, 2007;Al-Achkar et al, 2014;Kassogue et al, 2015). These findings were in agreement with this study.…”
Section: Genotypessupporting
confidence: 94%
See 1 more Smart Citation
“…The above findings were in agreement with a recent study conducted in Sudan (Muddathir et al, 2019). Many studies have focused on the relationship between GSTT1 polymorphism and the risk of CML in diverse ethnic groups (Bajpai et al, 2007;Al-Achkar et al, 2014;Kassogue et al, 2015). These findings were in agreement with this study.…”
Section: Genotypessupporting
confidence: 94%
“…The development of cancer results from an imbalance between exposure to carcinogens (endogenous and exogenous) and the capacity of various enzyme systems engaged in the activation or detoxification of Xenobiotics. Inter-individual genetic variation in xenobiotic metabolizing enzymes has been associated with cancer development, (Kassogue et al, 2015) and since such a metabolism constitutes an important line of defense against a variety of carcinogens, inherited differences in…”
Section: Introductionmentioning
confidence: 99%
“…Nahla A. et al (2016) in their study indicated that GSTP1 mutant allele may contribute significantly to susceptibility to CML in sample of Egyptian patients (12). In a study done in Moroccan patients(M),Yaya Kassuogue et al (2015) have concluded that the GSTT1 null genotype is associated with the development of CML in males but not in females (13). In patients of Argentina, Weich N et al (2016) came to conclusion that GSTM1 is significantly linked to poor molecular response to treatment of CML.…”
Section: Major Common Gene Polymorphisms In Chronic Myeloid Leukemiamentioning
confidence: 99%
“…The PCR reaction mixture consisted of 100 ng of genomic DNA, 1× of 10× Buffer (Invitrogen), 1.5 mM of MgCl2, 0.2 mM of each dNTP, 10 pM of each primer and 0.5 U of Taq polymerase (Invitrogen) completed to 25 µL with molecular grade water. The forwards and reverses primers used for GSTT1, GSTM1 and BCL2 as well as PCR amplification technical aspects were previously described in details by Kassogue et al [21,22]. DNA fragments were analyzed on a 2% agarose gel stained with 0.5 µg/mL ethidium bromide.…”
Section: Genotyping Of Gstm1 Gstt1 and Gstp1 Polymorphismsmentioning
confidence: 99%